Heating effect on quality characteristics of mixed canola cooking oils - Baig, Ayesha; Muhammad Zubair; Sumrra, Sajjad Hussain; Nazar, Muhammad Faizan; Zafar, Muhammad Nadeem; Jabeen, Kausar; Hassan, Muhammad Bilal; Rashid, Umer (BioMed Central, 2022)
Background: The subcontinent is famous for its variety of seasonal foods cooked in vegetable seed cooking oils at elevated heating. Oils are often of poor quality that effect to consumer health. The work, therefore, planned to examine the effects of heat on the quality of mixed canola cooking oils (MCCOs). MCCOs were analyzed by preparing volatile fatty acid methyl esters (FAMEs) and for physiochemical properties. Results: A major change was observed in the FAs composition of various MCCOs as coded K-1 to K-5. MCCOs were found rich in unsaturated 9-octadecanoic acid (oleic acid C18:1) and 9, 12-octadecadienoic acid (linoleic acid C18:2) along saturated octadecanoic acid (stearic acid C18:0). Results reveals that canola oil samples are mixed in the range of 4–30% with other vegetable oils and animal fats. The quality of canola cooking oils further reduced after heating to 100 °C, 200 °C and 350 °C, respectively. Quality parameters of MCCOs were significantly altered after heating and found as color (510–520 nm to 570–600 nm), mass 220–237 g to 210–225 g, volume 250 mL to 239 mL, pH (6.76–6.89), specific gravity (0.87–0.92), refractive index (1.471–1.475), saponification value (SV) (0.7–2.5), un-saponifiable matter (2.4–9.8%) and acid value (AV) (1.20–5.0 mg KOH). Conclusion: Heating of oils at elevated temperature have shown a significant effect on pH, specific gravity and un-saponifiable matter (p-value < 0.05). Large changes in the physicochemical parameters and FAs composition help to develop a conclusion that cooking at high temperatures affects the quality of mixed canola cooking oils.